THE PREMISES OF SYMBOLIC INTERACTIONISM IN BUCHI EMECHETA’S THE SLAVE GIRL AND THE JOYS OF MOTHERHOOD (NOBEL: Journal of Literature and Language Teaching, 2014)
Literature remains an important part of every society because of its didactic and aesthetic functions. From the preliterature era to the present, literature is still as a source with which to appreciate human creativity and burden to look at human experiences and actions, more critically, satirically and sometimes, pleasurably. Literature has the ability to stimulate human consciousness to reality and points to human folies. Through the major forms of literature, writers of all ages have been able to capture the social, political and cultural moods and experiences of their societies.